HIGH PRANDTL NUMBER MIXED CONVECTION CAVITY FLOW USING LATTICE BOLTZMANN METHOD - M.A. Taher; H.D. Kim; Y.W. Lee (European Scientific Journal, ESJ, 2013)
The mixed convection heat transfer and fluid flow behaviors in a lid–driven square cavity filled with high Prandtl number fluids at low Reynolds number have been studied using Thermal Lattice Boltzmann Method (TLBM). The LBM has built up on the D2Q9 model called the Lattice-BGK (Bhatnagar–Gross–Krook) model. The Lattice Boltzmann momentum and energy equations are considered simultaneously to solve the problem. Effects of non dimensional mixed convection parameter, namely buoyancy parameter or Richardson number (Ri) in presence of heat generation (q) with moving lid are discussed to investigate the thermal and fluid flow behaviors. It deals with continuing and comparison study of authors recent published work (Taher et al. 2013). The results are presented as velocity and temperature profiles as well as stream function and temperature contours for 0.50 ≤ Ri ≤ 10.0 and q ranging from 0.0 to 0.10 with other controlling parameters. It is found that LBM has good potential to simulate mixed convection heat transfer and fluid flow problems. The mixed convection parameter, Ri, provides an important measurement of the thermal natural convection forces relative to the mechanically induced lid-driven forced convection with heat generation (q) effects. Moreover, it is found that the overall heat transfer rate in terms of Nusselt number (Nu) are significantly increased with increasing Ri and decreased very slightly with increasing the values of heat generation. Finally, the simulation results have been compared with the previous numerical and experimental results and it is found to be in good agreement.